EVALUATION OF THE POTENTIALITY OF WFI/CBERS-3 SENSOR DATA FOR LAND USE AND LAND COVER CLASSIFICATION - Eduardo Eiji Maeda; Gustavo Felipe Balué Arcoverde; Antonio Roberto Formaggio; Yosio Edemir Shimabukuro (Revista Brasileira de Cartografia, 2008)
The high cost involved in the development and launching of optical orbital sensors makes the planning and study of the potential uses of their products necessary before their launch. CBERS-3 satellite is planned to be launched in 2008 and will carry on board, among other sensors, the Wide Field Imager Camera (WFI). Its technical characteristics will benefit users who need moderate spatial and high temporal resolution images. Then, the objective of this work is to simulate and evaluate the potentiality of a WFI/CBERS-3 image for land use and land cover classification in two landscapes with different characteristics. The first site is characterized by intensive agricultural area in São Paulo State located in the Southeast region of Brazil, and the second area is characterized by deforested areas in Mato Grosso State, located in the Amazon region. The simulation of the WFI/CBERS-3 images was made using two ETM+/Landsat-7 scenes. The obtained classification results achieved for both studied sites show that WFI /CBERS-3 images will be a useful source of information for land use and land cover classification. Key-words: Digital image processing, CBERS-3 satellite, WFI sensor, Image simulation.